Bisphenol A and selenium deficiency exposure induces pyroptosis and myogenic differentiation disorder in chicken muscle stomach - Wu, Di; Su, Yingying; Hu, Guanghui; Lin, Xu (Poultry science, 2024)
Bisphenol A (BPA), which is commonly found in the environment due to its release from the use of plastics and food overpacks, has become a major stressor for environmental sustainability and livestock and poultry farming health. Selenium (Se) deficiency causes structural damage and inflammatory responses to the digestive system and muscle tissue, and there is a potential for concurrent space-time exposure to nutritional deficiency diseases and environmental toxicants in livestock and poultry. The mechanisms of damage to chicken muscular stomach from BPA or/and Se deficiency treatment are still not known. Here, we established a chicken model of BPA (20 mg/kg) or/and Se deficiency (0.039 mg/kg) exposure, and detected histopathological changes in the muscular stomach tissue, the levels of iNOS/NO pathway, IL-6/JAK/STAT3 pathway, pyroptosis, and myogenic differentiation by H&E staining, immunofluorescence staining, real-time quantitative PCR, and western blot methods. The data revealed that BPA or Se deficiency exposure caused gaps between muscle fibers with inflammatory cell infiltration; up-regulation of the iNOS/NO pathway and IL-6/JAK/STAT3 pathway; up-regulation of NLRP3/Caspase-1-dependent pyroptosis related genes; down-regulation of muscle-forming differentiation (MyoD, MyoG, and MyHC) genes. The combination of BPA and Se deficiency was associated with higher toxic impairment than alone exposure. In conclusion, we discovered that BPA and Se deficiency caused myogastric pyroptosis and myogenic differentiation disorder. These findings provide a theoretical basis for the co-occurrence of animal nutritional deficiency diseases and environmental toxicant exposures in livestock and poultry farming, and may provide important insights into limiting the production of harmful substances.